2022
DOI: 10.11646/zootaxa.5174.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological variation analyses of Glandirana rugosa with description of a new species (Anura, Ranidae)

Abstract: Glandirana rugosa is known to include several geographic groups differing in sex chromosomes, and has been proven to be paraphyletic in mitochondrial phylogeny with respect to G. susurra. By analyzing genetic and morphological variation in a large number of individuals of Glandirana, we studied their taxonomic relationships. A mitochondrial DNA phylogeny, with the G. tientaiensis as outgroup, revealed two major lineages containing respectively (1) the East group of G. rugosa, G. susurra, and the Central and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Significant differences in the morphology and sex chromosome composition within a single species can sometimes lead to its classification as a separate species. Recently, the East Japan population distributed in eastern Japan with homomorphic sex chromosomes of G. rugosa was identified as a new species Glandirana reliquia , distinct from the remaining populations of G. rugosa , based on morphological and phylogenetic analyses (Shimada et al, 2022). Further detailed analyses of species exhibiting different characteristics of sex chromosomes between populations will provide insights into not only the evolutionary process of sex chromosomes but also speciation process in these species.…”
Section: Complex Sex Chromosome Systems In Amphibians and Reptilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant differences in the morphology and sex chromosome composition within a single species can sometimes lead to its classification as a separate species. Recently, the East Japan population distributed in eastern Japan with homomorphic sex chromosomes of G. rugosa was identified as a new species Glandirana reliquia , distinct from the remaining populations of G. rugosa , based on morphological and phylogenetic analyses (Shimada et al, 2022). Further detailed analyses of species exhibiting different characteristics of sex chromosomes between populations will provide insights into not only the evolutionary process of sex chromosomes but also speciation process in these species.…”
Section: Complex Sex Chromosome Systems In Amphibians and Reptilesmentioning
confidence: 99%
“…These results reveal the presence of shared genetic linkages (chromosome 7) between the sex chromosomes in both the ZW and XY populations of G. rugosa . Recent DArTseq analysis using individuals of the West Japan population and the related species G. reliquia (formerly the East Japan population of G. rugosa ) (Shimada et al, 2022) indicated that sex‐linked DNA markers were located on different homologous chromosomes, chromosome 3 in the West Japan population and chromosome 1 in G. reliquia , from the sex chromosomes in the ZW and XY populations (Miura et al, 2022). These results demonstrate that at least two turnovers of sex chromosomes occurred within G. rugosa and the related species G. reliquia .…”
Section: Diversity In the Sex Chromosome Origins In Amphibiansmentioning
confidence: 99%
See 1 more Smart Citation